2003
DOI: 10.1614/wt02-092
|View full text |Cite
|
Sign up to set email alerts
|

Winter Annual Weed Control with Fall-Applied Corn (Zea mays) Herbicides1

Abstract: Field studies were conducted during the 2000 to 2001 growing seasons to evaluate winter annual weed control and crop tolerance with fall-applied herbicides in corn at Belleville, IL. Atrazine, simazine, and rimsulfuron plus thifensulfuron applied in the fall controlled mouseear chickweed, henbit, and Carolina foxtail 93% or greater at planting the following spring. Flumetsulam controlled mouseear chickweed and henbit 98 and 93%, respectively, at planting. Metribuzin controlled mouseear chickweed and henbit 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 9 publications
1
53
2
Order By: Relevance
“…Fall herbicide applications have increased in popularity over the past several years, primarily because of increased occurrence of winter annual weeds (Krausz et al 2003). Although winter annual weeds offer the benefit of soil cover for erosion control, they can host insect pests, delay soil warming in the spring, and interfere with planting or spring tillage operations (Dahlke et al 2001;Venkatesh et al 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fall herbicide applications have increased in popularity over the past several years, primarily because of increased occurrence of winter annual weeds (Krausz et al 2003). Although winter annual weeds offer the benefit of soil cover for erosion control, they can host insect pests, delay soil warming in the spring, and interfere with planting or spring tillage operations (Dahlke et al 2001;Venkatesh et al 2000).…”
mentioning
confidence: 99%
“…Although winter annual weeds offer the benefit of soil cover for erosion control, they can host insect pests, delay soil warming in the spring, and interfere with planting or spring tillage operations (Dahlke et al 2001;Venkatesh et al 2000). Fall applications of herbicides may allow soils to warm more rapidly in the spring by reducing vegetative cover and may facilitate earlier planting of no-tillage crops by reducing winter annual weed biomass (Krausz et al 2003;Lee and Witt 2001). Fall applications also allow growers and applicators to spread out their spring workload and may eliminate or reduce the need for a burndown application before crop planting in notill systems (Dahlke et al 2001;Krausz et al 2003).…”
mentioning
confidence: 99%
“…The most common winter weed management tools utilized in no‐till corn/soybean production systems in Indiana are herbicides and winter cover crops. Winter annual weeds can be effectively controlled with herbicides in the fall (23,29) or the spring (30,32) but the effect of weed removal timing on SCN population density is unknown. Optimal herbicide application timing may enable these winter annual weeds to serve as “trap crops” for SCN.…”
Section: Potential Management Implicationsmentioning
confidence: 99%
“…Glyphosate is a systemic, non‐selective post‐emergence herbicide with no residual soil activity. The increase in adoption of GR corn and soybean cropping systems in the Midwestern region has decreased the use of soil residual herbicides in these cropping systems, which has been speculated to increase the severity of winter and spring weed infestations (4,7). For instance, during 1996 in the United States, the total soybean area treated with chlorimuron‐ethyl, glyphosate, imazaquin, and metribuzin in soybean production systems was 16%, 20%, 15%, and 11%, respectively (11).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers reported that fall applications of herbicides not only control winter annual weeds, but can also reduce the number of operations in spring (5,7). Numerous reports have shown the control of winter and spring annual weed species with application of residual herbicides in fall (3,7,9,10). However, studies that report the control of winter and spring annual weed species in corn and soybean with herbicide treatments applied in the spring of the previous year are limited.…”
Section: Introductionmentioning
confidence: 99%